Transcriptomics and metabolomics association analysis revealed the responses of Gynostemma pentaphyllum to cadmium - Zhou, Yunyi; Yao, Lixiang; Huang, Xueyan; Li, Ying; Wang, Chunli; Huang, Qinfen; Yu, Liying; Pan, Chunliu (Frontiers in Plant Science, 2023)
Gynostemma pentaphyllum an important medicinal herb, can absorb high amounts of cadmium (Cd) which can lead to excessive Cd contamination during the production of medicines and tea. Hence, it is crucial to investigate the response mechanism of G. pentaphyllum under Cd stress to develop varieties with low Cd accumulation and high tolerance. Physiological response analysis, transcriptomics and metabolomics were performed on G. pentaphyllum seedlings exposed to Cd stress. Herein, G. pentaphyllum seedlings could significantly enhance antioxidant enzyme activities (POD, CAT and APX), proline and polysaccharide content subject to Cd stress. Transcriptomics analysis identified the secondary metabolites, carbohydrate metabolism, amino acid metabolism, lipid metabolism, and signal transduction pathways associated with Cd stress, which mainly involved the XTH, EXP and GST genes. Metabolomics analysis identified 126 differentially expressed metabolites, including citric acid, flavonoid and amino acids metabolites, which were accumulated under Cd stress. Multi-omics integrative analysis unraveled that the phenylpropanoid biosynthesis, starch, and sucrose metabolism, alpha-linolenic acid metabolism, and ABC transporter were significantly enriched at the gene and metabolic levels in response to Cd stress in G. pentaphyllum. In conclusion, the genetic regulatory network sheds light on Cd response mechanisms in G. pentaphyllum.